Pendampingan Pencatatan Keuangan dan Digital Marketing pada UMKM Unin Kitchen Sebagai Bentuk Pengabdian Kepada Masyarakat: Pengabdian - Dewi Astuti; Meisya Wahyuni Adelana; Tuti Alawiyah; Deni Saeful Rizal; Nana Supriana (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study analyzes operational efficiency, financial record-keeping, and digital marketing strategies in bakery SMEs, focusing on Unin Kitchen. It examines internal business practices such as production management, digital promotion, and financial recording systems that support decision- making. The findings provide insights into the dynamics of bakery SMEs in Indonesia, particularly the integration of production and digital marketing. Practically, this research offers recommendations to improve operational efficiency, strengthen digital marketing strategies, and enhance product innovation, enabling Unin Kitchen to compete in both local and digital markets. The results may also serve as a reference for other SMEs facing similar challenges.